2011
DOI: 10.1039/c1cy00259g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of versatile MgO–ZrO2 mixed metal oxide nanoparticles and their applications

Abstract: Nano‐MgO/ZrO2 is prepared and used as catalyst for cross‐aldol condensation, Cbz‐protection of amines, reduction of aromatic nitro compounds and the synthesis of 1,5‐benzodiazepines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(56 citation statements)
references
References 79 publications
2
51
0
Order By: Relevance
“…Furthermore, XPS study for Mg1s region showed a single peak in position of 1304 eV which fits well with MgO structure (Fig. 5) [42]. In order to study elemental distribution of the Pd@MgO-CQD, elemental mapping was studied and results confirmed presences of C, Pd, and Mg in the structure (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Furthermore, XPS study for Mg1s region showed a single peak in position of 1304 eV which fits well with MgO structure (Fig. 5) [42]. In order to study elemental distribution of the Pd@MgO-CQD, elemental mapping was studied and results confirmed presences of C, Pd, and Mg in the structure (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Zirconium oxide (ZrO 2 ) is one such prominent metal oxide with amphoteric character [2][3][4], but which in pure form is catalytically inactive for transesterification under mild conditions [5] due to its weak basicity. Efforts to improve the base strength of ZrO 2 have focused on its modification by alkaline earth metals such as calcium [6][7][8] and magnesium [5,[9][10][11][12][13][14]. Such doped zirconias often exhibit a higher surface area, base strength, and stability relative to the parent individual metal oxide components, with Mg-Zr mixed oxides being promising candidates for reactions including Knoevenagel condensation [9,13], furfural-acetone aldol condensation [12], transesterification [5,15], and reduction of carbonyl compounds [16].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to improve the base strength of ZrO 2 have focused on its modification by alkaline earth metals such as calcium [6][7][8] and magnesium [5,[9][10][11][12][13][14]. Such doped zirconias often exhibit a higher surface area, base strength, and stability relative to the parent individual metal oxide components, with Mg-Zr mixed oxides being promising candidates for reactions including Knoevenagel condensation [9,13], furfural-acetone aldol condensation [12], transesterification [5,15], and reduction of carbonyl compounds [16]. In the case of aldol condensation, Sádaba et al [12] defined two distinct active sites for MgO-rich Mg-Zr mixed oxides: Mg-O-Mg and Mg-O-Zr sites, with the latter being more reactive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad absorption peak centered at 1425 cm ¹1 is believed to originate from the vibration of MgO NPs. 20 From the results mentioned above, it is concluded that the heat treatment at 420°C under a hydrogen atmosphere produced the hybrid material composed of MgO NPs and Mg-MOF-74, and the heat treatment at 530°C under a hydrogen atmosphere produced MgO NPs as the main component. In addition, the mean diameter of the MgO NPs was changed by the heating conditions.…”
mentioning
confidence: 99%